Hardware Implementation of Blowfish Algorithm for the Secure Data Transmission in Internet of Things. (2016) - Suresh, Manju; Neema, M.
Abstract: As Internet of Things (IoT) can be broadly used in many fields, the security of IoT is gaining importance. In IoT, all the devices are connected. If a hacker manages to enter the network, he may access confidential datas. So for IoT, an information transmission security mechanism is essential in addition to the authentication mechanism. Beginning with the concept of IoT, its architecture and security issues, this paper analyzes various security mechanisms for IoT and the significance of cryptography in IoT. An efficient cryptographic algorithm "Blowfish" is selected based on several comparisons. A modification in Blowfish algorithm is presented by changing its Function module 'F'. Comparison of original and modified blowfish algorithm is done by implementing both in Xilinx Virtex-5 XC5VLX50T FPGA using Verilog HDL and found that modified algorithm is efficient than the original in terms of encryption time by 16.9% and throughput by 18.7%.